Dielectrophoresis‐based 3D‐focusing of microscale entities in microfluidic devices. Issue 8 (30th August 2018) - Alnaimat, Fadi; Ramesh, Salini; Alazzam, Anas; Hilal‐Alnaqbi, Ali; Waheed, Waqas; Mathew, Bobby
Abstract: This article presents a validated mathematical model of a dielectrophoresis (DEP)‐based microfluidic device capable of 3D‐focusing microscale entities at any lateral location inside the microchannel. The microfluidic device employs planar, independently controllable, interdigitated transducer (IDT) electrodes on either side of the microchannel. The developed model is used for understanding the influence of different geometric and operating parameters on 3D focusing, and it comprises of motion equation, Navier–Stokes equation, continuity equation, and electric potential equation (Laplace equation). The model accounts for forces associated with inertia, gravity, buoyancy, virtual mass, drag, and DEP. The model is solved using finite difference method. The findings of the study indicate that the 3D focusing possible with the proposed microfluidic device is independent of microscale entity's size and initial position, microchannel height, and volumetric flow rate. In contrast, 3D focusing achievable with the microfluidic device is dependent on the applied electric potential, protrusion width of electrodes, and width of electrode/gap. Additionally, the lateral position of 3D focused can be controlled by varying the applied electric potential. The advantage of the proposed microfluidic device is that it is simple to construct while capable of achieving 3D focusing at any lateral location inside the microchannel.